LOG MOTIF AND RESERVOIR PROPERTIES IN THE CENTRAL MALAY BASIN - binti Mohd Anuar , Nor Aqilah (Universiti Teknologi PETRONAS, 2014)
The Malay basin is a Tertiary rift basin located in between Peninsular Malaysia and Vietnam offshore. A review on lithology, pressure, temperature and heat flow of the basin is conducted at two exploration wells; Tujoh-1 and Tangga-1. This study is carried out to investigate depositional environment and factors that controls overpressure in the basin. Using log motif and thermophysical properties interpretations, the reservoir quality and the main mechanism of overpressure will be discussed. Tidal bar and mouth bar are developed within distributary channels, along delta fronts and in the outer parts of estuaries. These facies have good reservoir qualities due to high lateral and vertical homogeneity of its morphology and grain size distribution. Previous works have revealed that the basin has high average heat flow (85 mWm-2 and 125 mWm-2) and geothermal gradient (45 °Ckm-1 and 60 °Ckm-1). A study on the subsurface pressure revealed that the top of overpressure occurs between 1800m to 2000m depth. The overpressure is confined in Group E for Tujoh-1 well and Group F for Tangga-1 well. The main cause for overpressure in the basin is believed due to disequilibrium compaction.